ISNI and traditional authority work - Amy Armitage; Mary Jane Cuneo; Isabel Quintana; Karen Young (JLIS.it, 2020)
This article describes key differences between ISNI (International Standard Name Identifier) and the authority work traditionally performed at libraries. Authority work is concerned with establishing a unique form of name for a person and collocating materials under that form of name. ISNI, on the other hand, is concerned with establishing a unique numerical identifier for each entity, and differentiating distinct entities. The focus of the work becomes identity management rather than the establishment of authorized name forms. This article looks not only at the differences in workflows, but also explains how these theoretical differences can affect the way librarians identify and collocate named entities. The focus is on the future, and how we can best use our skills to ensure that entities are properly differentiated and accessible to our patrons.